10 Hz rTMS over right parietal cortex alters sense of agency during self-controlled movements - Ritterband-Rosenbaum, Anina; Karabanov, Anke N.; Christensen, Mark S.; Nielsen, Jens Bo (Frontiers in Human Neuroscience, 2014)
A large body of fMRI and lesion-literature has provided evidence that the Inferior Parietal Cortex (IPC) is important for sensorimotor integration and sense of agency (SoA). We used repetitive transcranial magnetic stimulation (rTMS) to explore the role of the IPC during a validated SoA detection task. 12 healthy, right-handed adults were included. The effects of rTMS on subjects’ SoA during self-generated movements were explored. The experiment consisted of 1/3 self-generated movements and 2/3 computer manipulated movements that introduced uncertainty as to whether the subjects were agents of an observed movement. Subjects completed three sessions, in which subjects received online rTMS over the right IPC (active condition), over the vertex (CZ) (sham condition) or no TMS but a sound-matched control. We found that rTMS over right IPC significantly altered SoA of the non-perturbed movements. Following IPC stimulation subjects were more likely to experience self-generated movements as being externally perturbed compared to the control site (P=0.002) and the stimulation-free control (P=0.042). The data support the importance of IPC activation during sensorimotor comparison in order to correctly determine the agent of movements.